Pengaruh Pendidikan Guru Penggerak terhadap Peningkatan Kompetensi Pedagogik Guru di Provinsi Maluku - Veny Yohan Sari; Izaak H. Wenno; Sumarni Rumfot (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
The low teacher participation in the Guru Penggerak Program (GPP) raises concerns about its impact on pedagogical competence. This study analyzes the influence of GPP and achievement motivation on improving teachers' pedagogical competence in student-centered learning in Maluku Province. Using a correlational quantitative approach, data were collected through questionnaires targeting the 9th cohort of GPP teachers. Results show that both GPP and achievement motivation significantly affect pedagogical competence individually and jointly. This indicates that teachers involved in GPP tend to demonstrate stronger capabilities in designing safe, effective, and engaging learning environments. These findings support the importance of expanding and strengthening the implementation of GPP as a key strategy for enhancing teacher quality.